2014
DOI: 10.2478/hukin-2014-0045
|View full text |Cite
|
Sign up to set email alerts
|

Game-Related Volleyball Skills that Influence Victory

Abstract: The aim of the present study was to identify the volleyball skills that discriminate in favour of victory. Twenty-four games (n=24) from the Senior Men’s Volleyball World Championship played in Italy in 2010 were chosen and analyzed with Data Volley software. The discriminating function was used to identify the discriminating variables, using a canonical structuring coefficient of |SC| ≥ .30. The results suggest that service points, reception errors, and blocking errors were the discriminating variables that i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
63
1
15

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 74 publications
(85 citation statements)
references
References 16 publications
6
63
1
15
Order By: Relevance
“…A team performing more reception actions is likely to lead to more errors in the same actions. Several studies have found an association between reception eff ectiveness and eff ects on the result of the match (Silva et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A team performing more reception actions is likely to lead to more errors in the same actions. Several studies have found an association between reception eff ectiveness and eff ects on the result of the match (Silva et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…It is not enough to just carry out more reception actions, but to execute them with excellence; not to obtain error in the reception is a factor that distinguishes the performance of the teams (Silva, Lacerda & João, 2014, García-Alcaraz, Palao & Ortega, 2014.…”
Section: Discussionmentioning
confidence: 99%
“…Sendo que dentro da sequência lógica do jogo de Voleibol, se diferenciam várias fases ou complexos de jogo (Afonso, Esteves, Araújo, Thomas, & Mesquita, 2012;Costa, Caetano, et al, 2011;João et al, 2010;Marcelino, Mesquita, Sampaio, & Moraes, 2010;Palao, Santos, & Ureña, 2004;Silva, Lacerda, & João, 2014;Zetou, Moustakidis, Tsigilis, & Komninakidou, 2007), a investigação realizada no domínio da Análise de Jogo tem vindo a destacar a preponderância do Complexo de Jogo I ou side-out (KI) no resultado final de jogo (Palao et al, 2004;Palao, Santos, & Ureña, 2005;Yiannis & Panagiotis, 2005;Zetou et al, 2007) que é suportado por Rocha e Barbanti (2004) que concluíram que dois fatores influenciam a qualidade do ataque em KI, a receção e o destino do ataque, também Afonso, Esteves, Araújo, Thomas, e Mesquita (2012) concluem sobre a importância da receção na determinação da dinâmica ofensiva em KI, quando refere que todas as investigações apresentam receções excelentes em amostras de alto nível, seniores masculinos (acima dos 50%), o que equivale a dizer que KI oferece condições melhores de finalização do ataque, em relação aos demais complexos.…”
Section: Introductionunclassified
“…In another study of Silva, Lacerda, Joao (2014) shows that service points, reception errors, and blocking errors were the discriminating variables that identify the final outcome of the match (won/loss). Moreover, successful service points were the major variable most likely associated with match success (won).…”
Section: Is It Possible To Estimate Match Results In Volleyball: a Newmentioning
confidence: 99%